Systemic loops and liquidity regulation - Aldasoro, Iñaki; Faia, Ester (Journal of Financial Stability, 2016)
Banks are typically exposed to spirals between liquidity scarcity and solvency risk. We build a network model of optimizing banks featuring contagion on both sides of balance sheets: runs on short term liabilities and banks’ liquidity hoarding induce liquidity freezes; fire sale externalities and interconnected debt defaults produce asset risk. We use the model, which is calibrated to European data via simulated method of moments, to study the effects of phase-in increases of liquidity coverage ratios. Interestingly we find that the systemic risk profile of the system is not improved and might even deteriorate. Based on those insights we propose an alternative approach: differential (across banks) application of coverage ratios based on a systemic importance ranking help to mitigate the externalities and deliver a much more stable system.